The Relationship Between Self-Care and Quality of Life Among Patients with Type 2 Diabetes - Hakim Tobroni HR; Nirmala K.S; Evi Tunjung Fitriani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Diabetes Mellitus (DM) Type II requires consistent self-care to maintain an optimal quality of life. However, DM patients often neglect self-care when they feel their condition is improving, potentially leading to a decline in their quality of life. This study aims to determine the relationship between self-care practices and the quality of life of DM Type II patients in Putuk Hamlet, Banaran Village, Kandangan District, Kediri Regency. This study used a correlational analytic design with a cross-sectional approach. The study sample consisted of 38 respondents selected using the simple random sampling technique from the population of DM Type II patients in the area. The independent variable was self-care and the dependent variable was quality of life. Data were collected using a questionnaire and analyzed using the Spearman test. The results of the study showed that the better the self-care implemented, the higher the quality of life of DM Type II patients. The Spearman test confirmed a significant relationship between self-care and the quality of life of diabetes mellitus patients, with a value of  = 0,000 (< α =0,05). There is a significant relationship between self-care and the quality of life of DM Type II patients. The implication is that the Kandangan Community Health Center is advised to enhance health education efforts, such as providing leaflets on self-care, as practical guides that can help patients consistently apply self-care at home to improve their quality of life.